2020
DOI: 10.1155/2020/3815397
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Creep Characteristics of Cemented Backfill in a Goaf under Water Pressure

Abstract: As the groundwater environment changes in a goaf, the creep deformation of the backfill underwater pressure is worthy of attention. This paper takes the undercut goaf filling in the Yuzhou section of the middle route of the South-to-North Water Transfer Project as an example. Grading loading creep testing of the backfill under different water pressures was carried out using equipment developed by our research team. Based on the experimental results, the following key points were observed: (1) under the same ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Hashiba [27] considered rock strength and creep life theory under the influence of moisture, and obtained the relationship between rock strength and creep life under dry and wet conditions. Zhang [28] et al subjected the filling body of the goaf to graded loading creep tests under different water pressures. The results showed that the mechanical properties of the filling body decreased with increasing water injection pressure.…”
mentioning
confidence: 99%
“…Hashiba [27] considered rock strength and creep life theory under the influence of moisture, and obtained the relationship between rock strength and creep life under dry and wet conditions. Zhang [28] et al subjected the filling body of the goaf to graded loading creep tests under different water pressures. The results showed that the mechanical properties of the filling body decreased with increasing water injection pressure.…”
mentioning
confidence: 99%